Financial Sanctions and Economic Growth: An Intervention Time-series Approach - Samira Heydarian; Mosayeb Pahlavani; Seyed Hossein Mirjalili (International Economics Studies, 2021)
In the present study, the authors examined the impact of financial sanctions on economic growth using Iran's data and intervention time-series analysis over the period 2005-2017. Financial sanctions targeted the country's financial resources and increased interest rates and medium- and long-term financing costs. In general, financial sanctions adversely affected the financial sector. In this regard, blocking of assets and restricted access to financial and foreign exchange resources, depreciated domestic currency, reduced investment, exports, and production along with increased inflation and unemployment ultimately reduced economic growth. The results indicated the effectiveness of financial sanctions on economic growth in the short-run. However, during the third period (2010-2014), when severe and multilateral financial sanctions are imposed, the coefficient is negative (0.54), which is higher, compared to the other periods. As the economic sanctions of Iran have intensified, the economic growth has slowed down. Nevertheless, in the long run, financial sanctions have had a weaker negative effect of 0.19 on the economic growth.
Keywords: F51; O47; O53; 330; Financial Sanctions; Economic Growth; Intervention Model; Iran's Economy